Soybeans Competitiveness with Morning Glory - PICCININI,F. (2016)
Weeds interfere negatively on development, yield and quality of soybeans (Glycine max). Inadequate weed control by herbicide use can select for resistant or tolerant biotypes, leading to a shift in the weed flora. An example is the increase of incidence of morning glory (Ipomoea spp.) in soybeans growing areas in South Brazil. The aim of this study was to determine the competitiveness of soybeans intercropped with I. triloba, I. indivisa and I. purpurea through a replacement experiments series. Greenhouse experiments were conducted in a completely randomized design with four replications. The first experiment was carried out aiming to get the plant population while total plant dry mass remained constant. Other experiments were done under replacement series experiments with soybeans and morning glory ratios of 100:0, 75:25, 50:50, 25:75 and 100:0 using the 250 plant m-2 defined by the preliminary experiment. Leaf area, root and shoots dry mass were assessed. Diagrams along with index interpretation were used to performed a competitiveness analysis. Soybeans showed greater competitiveness as I. triloba, I. purpurea and I. indivisa species for the leaf area, root and shoots dry mass variables. Intraspecific competition prevails between soybean plants whilst interspecific competition prevails for morning glory.